Participation in Boys & Girls Clubs Of Winnipeg is Associated With Health, Social and Education Outcomes Among First Nation Children - Enns, Jennifer; Brownell, Marni; Nickel, Nathan; O’Laney, Kim; Murdock, Nora; Sarkar, Joykrishna; Burland, Elaine; Chartier, Mariette; Chateau, Dan; Katz, Alan (International Journal of Population Data Science, 2020)
Introduction The Boys & Girls Clubs of Winnipeg (BGCW) provide out-of-school programs to children and youth living in low-income neighbourhoods in Winnipeg, Canada. These programs aim to set participants on a path to success by supporting healthy behaviours, academic achievement and social skills. First Nation children and youth make up a substantial proportion of BGCW participants, but there are few empirical data available on how the programs influence health, social and education outcomes in this population. Objectives and Approach We linked BGCW attendance records for all Manitoba children born 1987-2010 to the individual-level administrative health, social and education data in the population-based Data Repository at the Manitoba Centre for Health Policy in Winnipeg. The comparison group of non-participants was matched on age and neighbourhood of residence. We narrowed the cohort to First Nation participants by linking to datasets containing First Nation identifiers. Education outcomes were examined using a generalized additive model, and health and justice system outcomes with a time-to-event model, adjusted for socioeconomic status, mother's mental health and age at first birth, and involvement in the child welfare system. Results 3,754 First Nation children and youth participated in BGCW from 2005-2016. The comparison group comprised 23,593 First Nation children and youth. Greater BGCW participation was associated with higher likelihood of performing well in grade 3 numeracy, but not other education outcomes (grade 3 reading, grade 7 student engagement or mathematics, grade 7/8 reading/writing, or graduating high school). Greater BGCW participation was also associated with lower risk of becoming involved with the justice system among youth aged 12-17 (i.e., lower risk of being charged with a crime) and with lower risk of teen pregnancy. Conclusion / Implications Participation in BGCW programs may contribute to improved health, justice and education outcomes for First Nation children and youth in Winnipeg.